A family guide to spiritual warfare : strategies for deliverance and healing - Beckman, Kathleen; Doktorczyk, Stephen S. (New Hampshire, Manchester : Sophia Institute Press, 2020)
Demons wage war against families because families are vital to God's plan of salvation. This stark reality requires that your family members become well-trained spiritual warriors who actively secure your home and fight to keep it off-limits to demonic activity. In A Family Guide to Spiritual Warfare, Kathleen Beckman offers you potent advice from her 12 years of active participation on an exorcist's team. She shows you how to clean up your household by cultivating in your family a civilization of love and how to withstand the spiritual attacks that inevitably come to destroy the harmonious family life you create.
Includes bibliographical references.
Keywords: Parent and child -- Religious aspects -- Christianity; Families -- Religious aspects -- Christianity; Demonology -- Baptists, [Catholic Church, etc.]; Exorcism; Parenting -- Religious aspects -- Christianity; Child rearing -- Religious aspects -- Christianity; Child rearing -- Religious aspects -- Christianity; Exorcism; Families -- Religious aspects -- Christianity; Parent and child -- Religious aspects -- Christianity; Parenting -- Religious aspects -- Christianity